Management and utilization of mangroves in Asia and the Pacific. (Rome FAO, 1982)
FAO environment paper ; 3
Keywords: Mangrove fisheries--Asia; Oceania--Management.; Mangrove forests--Asia; Oceania--Management.; Mangrove swamps--Economic aspects--Asia; Oceania; Mangrove forests--Economic aspects--Asia; Oceania